1998
DOI: 10.1016/s0014-5793(98)00130-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a lipoxygenase inhibitor in A431 cells as a phospholipid hydroperoxide glutathione peroxidase

Abstract: An endogenous lipoxygenase inhibitor, purified from the cytosol of human epidermoid carcinoma A431 cells, was analyzed by N-terminal microsequencing and mass spectrometric analysis. The inhibitor was purified by SDS-PAGE, then subjected to in-gel CNBr cleavage and trypsin digestion. The N-terminal sequence data obtained from a 6^8 kDa band of ingel CNBr cleavage and the three isolated peptides of in-gel trypsin digestion, and the C-terminal peptide sequence from matrix-assisted laser desorption ionization mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 29 publications
(25 reference statements)
1
21
0
Order By: Relevance
“…In accordance, 13(S)-HPODE but not H 2 O 2 counteracted M-DSP-or GPx-1-induced 5-LO suppression. Although GPx-4 has been reported to inhibit 5-LO activity in differentiated HL-60 and BL41-E95-A cells (11), RBL-2H3 cells (14) and A431 cells (13), it is unlikely that this peroxidase is the M-DSP, since GPx-4 is a monomeric 19 kDa protein (48) that is not sensitive to mercaptosuccinate (5) and requires millimolar concentrations of thiols for efficient inhibition of 5-LO activity (11,12). Interestingly, Coffey et al (49) reported about a cytosolic protein of mononuclear phagocytes that reduced 5-LO activity in broken cell preparations and prolonged the lag phase of soybean LO, which was reversed by addition of 13(S)-HPODE.…”
Section: Activation Of 5-lipoxygenase By Ca 2ϩmentioning
confidence: 99%
“…In accordance, 13(S)-HPODE but not H 2 O 2 counteracted M-DSP-or GPx-1-induced 5-LO suppression. Although GPx-4 has been reported to inhibit 5-LO activity in differentiated HL-60 and BL41-E95-A cells (11), RBL-2H3 cells (14) and A431 cells (13), it is unlikely that this peroxidase is the M-DSP, since GPx-4 is a monomeric 19 kDa protein (48) that is not sensitive to mercaptosuccinate (5) and requires millimolar concentrations of thiols for efficient inhibition of 5-LO activity (11,12). Interestingly, Coffey et al (49) reported about a cytosolic protein of mononuclear phagocytes that reduced 5-LO activity in broken cell preparations and prolonged the lag phase of soybean LO, which was reversed by addition of 13(S)-HPODE.…”
Section: Activation Of 5-lipoxygenase By Ca 2ϩmentioning
confidence: 99%
“…Moreover, purified inhibitor exhibits peroxidase activity using phosphatidylcholine hydroperoxides as the substrate. We therefore conclude that the endogenous inhibitor of arachidonate metabolism present in A431 cells is indeed a PHGPx [23]. PHGPx was first purified from pig liver [53] and then from rat testis [43].…”
Section: Structural Determination and Oxygenase-inhibitory Specificitmentioning
confidence: 72%
“…Since the discovery of the endogenous inhibitor from the cytosolic fraction of A431 cells, which regulates the cellular arachidonate metabolism [5], two major breakthroughs have been achieved in our series of studies. The first one is the purification of the endogenous inhibitor from the cytosolic fraction of cells which regulates the arachidonate metabolism [9], and the subsequent identification of the entity of this inhibitor as a PHGPx [23]. The second one is the creation of a stable PHGPx-depleted A431 cell line, which provides direct evidence showing that the endogenous PHGPx indeed plays a functional role in down-regulating the 12(S)-lipoxygenase and cyclooxygenase 1 activities in A431 cells [7].…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of the purified inhibitor protein was analyzed by a high-sensitivity microsequencer and mass spectrometer, and the sequence data matched those of human PHGPx [8]. Moreover, the purified inhibitor exhibited peroxidase activity using phosphatidylcholine hydroperoxides as a substrate [8]. We therefore concluded that the 12-lipoxygenase inhibitor present in A431 cells was PHGPx.…”
mentioning
confidence: 82%